Edukasi Prenatal dalam Upaya Peningkatan Brestfeeding Self Efficacy - Ulfa Husnul Fata; Anita Rahmawati (STIKes Patria Husada Blitar, 2016)
The percentage of exclusive breastfeeding will be decreased in line with the raise of babyâ€™s age. The primary factors that make mothers do not give or stopped exclusive breastfeeding are the lack of breastfeeding self efficacy so that mothers feel that they do not have enough breastfeed for their baby. The aim of the research was to find out the effectiveness of ASI prenatal education toward breastfeeding self efficacy. The research design was post test only control group design. The population was all pregnant women in the third trimester of Puskesmas Kepanjen Kidul Kota Blitar. The sample was 40 taken by purposive sampling and divided into treatment group and control group by simple random sampling. The treatment group was given education on ASI and lactation on pregnancy period. Education was completed by presenting mothers who had been succeed in giving exclusive breastfeeding (giving testimonial) to share their experience in giving breastfeed. After that, all respondents breastfeeding self efficacy level were measured with BSES-SF in between the second day until 2 weeks of postpartum. The result showed that the average score of breastfeeding self efficacy of treatment group was 61,15Â±5,566 and the control group was 49,85Â±9,438. The data analysis by independent t test showed that there was an effect of prenatal education toward breastfeeding self efficacy(p=0,000, ï¡<0,05). It was expected that prenatal education on lactation which presented the breastfeeding testimonial were given during the pregnancy period in order to enhance mothersâ€™ breastfeeding self efficacy.